Exploring Water Pollution Subtopics: Validation of Histological Preparations - Pahlevi, Muhammad Rizza; Habiburrahman , Novan; Zubdatu Zahrati; Lestariningsih; Infantri Humau (Universitas Kristen Cipta Wacana, 2024)
This study aims to enhance understanding of water pollution through the use of histology preparations as educational tools for the sub-topic of water pollution in Grade X high school or equivalent. The research employs a descriptive method with a skinative approach. Water pollution is defined as the introduction of organisms, substances, energy, and/or other components into water due to human activities, resulting in a decline in water quality that affects its intended function. Histology preparations serve as a medium to assess the condition of organisms' tissues in rivers. Histology is essential for studying the normal tissue structure of organs or other body parts, addressing both anatomical and physiological aspects. Under a microscope, tissue preparations allow for the study of normal and abnormal tissue structures. Quality preparations must meet two criteria: identification, from organ collection through to observation, requiring expert handling; and cleanliness, assessed by the absence of air bubbles and the overall cleanliness of the preparation.